Analysis and Audit of Equity Capital in Joint-Stock Companies - Abdujaborova M.T., (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
One of the most important goals of any enterprise is to maintain a source of income, i.e. own capital. Equity is property that is free from liabilities and is used as assets. The financial stability of the enterprise is determined by the structure and value of equity capital (EC). The structure, dynamics and value of equity capital influence the adoption of managerial decisions of a short-term and long-term nature.